A Psychosocial Linguistic Exploration of the Use of Alcoholic as a Social Label of Self-identity in AA and 12-Step Programs. Issue 1 (2nd January 2018) - Tkach, Michael J.
ABSTRACT: The use of linguistic labeling of oneself as an alcoholic in Alcoholics Anonymous meetings is in direct contrast to the patient-centered language approach recommended by the American Psychological Association. Furthermore, reductionist self-identification with symptoms is suggested to devalue the individual at the cost of recognizing the uniqueness of personhood. In spite of this, the continued use of the label alcoholic as a moniker for a social label of self-identity is still embraced by many within the recovery community. The author explores the theoretical underpinnings of the use of this term as well as any potential psychological influence of the use of this term may have on those who self-identify as an alcoholic and concludes by recommending that the term be reserved for use by individuals in recovery as a self-label of self-identity rather than being a label of self-identity imposed by others.